Pertanggungjawaban Pidana Korporasi Sebagai Pemberi Pinjaman Online - Pratiwi, Ni Wayan Widya; Ibrahim, Aji Lukman (Kertha Patrika, 2023)
The value of fintech lending loans in Indonesia is one of the most significant contributors to increasing financial inclusion. However, like two sides of a sword, disruption by fintech lending also greatly impacts society. Thus, the problem of legal issues is raised around the corporate criminal liability model by online lenders and appropriate sanctions for online loan transactions in the future—perpetrators of corporate crime in online loans. The type of research used is normative juridical, with a case approach, conceptual approach, and statutory approach. The results of the study explain that a person who consciously (willens en wetness) creates legal consequences (voltooid delict/delict met matrieele omschrijving) and in his knowledge intentionally (opzet) commits an act which can be punished by him (strafbaar feit). As well as the provision of administrative sanctions in the form of criminal fines that are equivalent to returning the rights of victims in crimes that have an economic loss value and also the need for risk mitigation in suppressing the growth of online loan cases.